Pengungkapan Diri pada Instagram Instastory - Mahardika, Riangga Diko; Farida, Farida (Faculty of Communications Science, Dr. Soetomo University, 2019)
This research departed from the self-disclosure of internet users through uploading their activities. This research aims to analyse an individual's self-disclosure in the Instagram's feature of Instastory. It employs theories, such as self-disclosure, phenomenology, and motivation theory to analyse self-disclosure in Instastory. This research utilise qualitative approach and descriptive method. Data are gathered through observation, interviews, and documentation. There are three key informants with the determined characteristics such as follower and viewer amount, and time availability of the interviewee to be researched and interviewed. According to the self-disclosure dimension, analysis of this research contains frequency, valency, truth, aims, and intention and intimacy shows that self-disclosure depends on mood and other party's demands. And its contents are delivered according to their own needs.